Comparing the immune response and protective effect of COVID-19 vaccine under different vaccination strategies - Tianyi Zhao; Xiaoping Huang; Yuelong Shu (Human Vaccines & Immunotherapeutics)
Although highly infectious respiratory viral infections spread rapidly, humans have evolved a precise and complex immune mechanism to deal with respiratory viruses, with strong intrinsic, highly adaptive and specific humoral and cellular immunity. At the same time, vaccination against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is one of the most cost-effective and efficient means of preventing morbidity, severe illness, and death from Coronavirus disease 2019 (COVID-19). As the global epidemic of COVID-19 continues to evolve and vaccines are being developed, it is important to conduct studies on immunization strategies to optimize vaccination strategies when appropriate. This review was conducted to investigate the relationship between the immune response and the protective effect of different vaccination scenarios (including booster, sequential and hybrid immunity), and to provide a basis for the optimization of vaccination strategies and the development of new vaccines in the future.